PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG MENYIMPAN DANA DALAM BADAN HUKUM KOPERASI ILEGAL DI DINDONESIA STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 3 K/PDT.SUS-PAILIT/2019 - Muammar Adil Daffa (2022)
Cooperatives in carrying out their business activities, may not conflict with Article 83 of the Cooperative Law. however, recently cooperatives have begun to appear that deviate from the provisions of Article 83 in carrying out their business activities. One example is KSP Pandawa Mandiri Group, which in carrying out its business activities as a Savings and Loans Cooperative is based on a Savings and Loans Business License Number: 260/SISP/Dep. 1/IV/2015 dated 7 April 2015 issued by the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia. That at first, the KSP Pandawa Mandiri Group in carrying out its business activities was in line with the permit it had, where the KSP Pandawa Mandiri Group provided savings and loan facilities to its members. However, in the process of developing these business activities, KSP Pandawa Mandiri Group requires a sizable amount of capital, so that it can provide a larger loan ceiling to its members. The path taken by the KSP Pandawa Mandiri Group is to open a new sub-business called "Pandawa Group" as a sub-business activity in the field of raising public funds (customers who are not members of the KSP Pandawa Group), where in this case Salman Nuryanto as the head of the KSP Pandawa Mandiri Group provide promises to Pandawa Group customers in the form of Return Income in the form of 10% (ten percent) interest every month from the funds raised by the customers. Article 16 paragraph (1) of Law Number 10 of 1998 concerning Banking which states: "Every party carrying out activities to collect funds from the public in the form of savings must first obtain a business license as a Commercial Bank or Rural Bank from the Management of Bank Indonesia, unless if the activity of collecting funds from the community is regulated by a separate law. The customer protection that can be provided by the state in the KSP Pandawa Group case is legal protection in the form of repressive means, where through the court the rights of the customer are given, so the customer is able to get his rights back through the results of the auction of assets owned by Nuryanto as the owner of the KSP Pandawa Group itself.